The challenges of a business analysis in the growing complexity of corporate structure - Kerstin Sindt (2016)
This paper argues that the success of a business analysis in the complex organizational structure depends on the knowledge management system in use, the degree of internal corporate communication, and the ability to establish trust to employees.
Keywords: organizational structure; business analysis; knowledge management; communication; trust